B. ANIMALIS AND THE LECTIN OF B. SUBTILIS DIFFERENTLY REGULATE CYTOKINES PRODUCTION BY MACROPHAGES IN TUMOUR-BEARERS - N.I. Fedosova; N.L. Cheremshenko; S.V. Gogol; T.V. Symchych; I.M. Voyeykova; О.O. Lykhova; V.F. Chekhun (Biotechnologia Acta)
By producing a variety of soluble factors, including cytokines, macrophages (Mph) modulate the activity of other immune cells and have direct effects on cancer cells. This makes Mph a promising target for cancer immunotherapy.